CONTEMPORARY WAYANG KULIT PERFORMANCE: A CRISIS IN JAVANESE CULTURE? - Yosep Bambang Margono S (Soegijapranata Catholic University, 2003)
Wayang kulit or shadow puppet theater performance has been greatly changing. Changes occur in many aspects such as in terms of the duration or length of the peliormance, its structure, the number of dalang who performs it,as well as the number of female singers (sindhen or waranggana) who accompany the dalang. Consequently, now wayang kulit performance is seen more as tontonan (entertainment) than as tuntunan (moral teachings). One of the main factors of this big change is the intrusion of western culture into Indonesia in general and Java in particular. This results in the reluctance of the young, especially, in watching this form of traditional art. Therefore, the changers) in the performance of wayang kulit or shadow theater is one of the efforts to make thisform of traditional art survive.